(untitled) (Research, Society and Development, 2024)
Phonophoresis is presented as a strategy to increase the permeability of body tissues and consequently enhance the activity of the antioxidant defense system. In this perspective, this study aimed to verify the effects of the naringin/β-cyclodextrin complexed gel associated with therapeutic ultrasound on oxidative biomarkers after musculoskeletal injury in rats. This is a laboratory study with a quantitative approach. Adult male Wistar rats were equally distributed into five different groups (n=40): control, muscle injury, naringin/β-cyclodextrin complexed gel, therapeutic ultrasound, and therapeutic ultrasound associated with the naringin/β-cyclodextrin complexed gel. The gastrocnemius muscle was injured with mechanical impact. Treatment was applied at intervals of 2, 12, 24, 48, 72, and 96 hours after injury. Lipid peroxidation, superoxide dismutase activity, and catalase activity were evaluated. The UTP + NAR group showed a statistically significant reduction in MDA levels (1.16 ± 0.16 nmolMDA/mg protein vs 7.22 ± 0.42 nmolMDA/mg protein; p<0.05), SOD activity (0.04 ± 0.01 SOD/mg protein vs 0.79 ± 0.09 U/mg protein; p<0.05), and CAT activity (0.006 ± 0.001 CAT/mg protein vs 0.622 ± 0.032 U/mg protein; p<0.05) when compared to the untreated group. There was no statistically significant difference between the UTP + NAR and NAR groups in all variables analyzed. These results suggest that the use of the naringin/β-cyclodextrin complexed gel associated with therapeutic ultrasound after musculoskeletal injury is effective in attenuating lipid peroxidation and enhancing the antioxidant system.